(untitled) (Journal of Applied Oral Science, 2011)
Tele-health is more than an innovative alternative; it is an excellent tool that enables access to health and education in health, making it possible to minimize distances, optimize time and reduce costs. Based on these advantages, some Brazilian Universities have used these actions in strategies of education, research and extension, aiming at the application of Tele-health in Brazil. In that way, the Bauru School of Dentistry - University of São Paulo (FOB-USP) has applied the use of information and communication technologies in health by means of a "Tele-Health League" (TL), in order to diagnose, prevent and treat diseases, in addition to educate the population and health services. Objective: The present study aims to introduce the characteristics of the Tele-Health League of FOB-USP, as well as the development of its projects. Material and Methods: The Tele-Health League consisted as a Diffusion Course approved by the Provost of Culture and Academic Extension of the University of São Paulo. It is composed as a large group enclosing professoriate coordinator, academician principal, contributing professors and league members, those, diversified between undergraduates students, graduated, health employees, technology and information areas. The participant members are evaluated by the presence frequency (minimum of 85%), and by the performance of tests and paperwork about the theoretical content provided. Results: In four years of activities, the TLFOB-USP obtained a high satisfaction index (90%), an increased number of vacancies due to the interest to become a member, more commitment of the professors of the University and the accomplishment of association with other Brazilian leagues. It is emphasized that the approval percentage of the course results in approval from approximately half of its members. Also, it is important to identify and repair the causes related to the quitting of some members. Conclusions: The results showed that the TLFOB-USP members, adjoining to the professor's participants, develop projects in Tele-helth, in Tele-aid and Tele-education areas, thus resulting in the involvement of the University and the community.